Participation in group music therapy: A preliminary study of the experiences and perceptions of adolescents who stammer. (September 2021) - O'Donoghue, Jessica; Egan, Gráinne; Moss, Hilary; Clements-Cortes, Amy
Highlights: Findings support group music therapy with adolescents who stammer. Participants described the group sessions as fun and enjoyable. Participants experienced increased confidence and peer support. Participants recommended music therapy alongside speech and language therapy. Abstract: Music therapy and music-based interventions are increasingly used in the treatment of speech, language, and communication needs, and music therapy has been extensively applied to adolescent groups. To date, however, there has been no published work examining music therapy for adolescents who stammer. The aim of the current study was to explore adolescents' experiences and perceptions of a group music therapy intervention. Four adolescents who stammer participated in semi-structured interviews examining their experience of group music therapy intervention. The music therapy group intervention consisted of five therapeutic sessions conducted at a summer camp for children and adolescents who stammer. Analysis of in-depth, semi-structured interviews revealed four main themes and several subthemes. Recurrent themes revealed a variety of psychosocial benefits related to the experience of group music therapy, such as developing new friendships and facilitating peer support, increasing self-confidence and self-expression. There was also an emphasis on fun and enjoyment. This paper highlights a number of key benefits of music therapy for adolescents who stammer. These preliminary results highlight the potential of music therapy for adolescents who stammer, and the role of addressing psychosocial aspects of stammering within this creative arts intervention.